CEO turnover, sequential disclosure, and stock returns - Hu, Jiayin; Liu, Laura Xiaolei; Liu, Chloe Yue; Qu, Hao; Zhang, Yingguang (Review of Finance, 2025)
Abstract We document that firms experience large negative stock returns during, and positive returns following, the first informational events after forced CEO turnovers. This V-shaped return pattern is driven by the strategic sequential disclosure of bad news and good news, aligned with incoming CEOs’ incentives to manage expectations. The pattern is more pronounced when these incentives are stronger, such as when firms earn higher stock returns and have higher valuation uncertainty leading up to the informational events. Evidence from firms’ earnings surprises, analysts’ forecast revisions, and large language model-based measures of disclosure behavior indicates that incoming CEOs often initially release bad news about realized and short-term earnings, projecting a broadly pessimistic outlook for the firm’s future performance, and subsequently disclose favorable news about longer-term earnings prospects. Our findings suggest that investors make the costly mistake of failing to discern the incentives behind managers’ disclosure.